القواعد الفقهية لوسائل الاثبات في الفقه المالكي - بن حفاف عتيقة; غليسات فاطمة الزهراء (جامعة عمار ثليجي الاغواط, 2024)
الملخص: منأهمأبوابالفقهالإسلاميالقواعدالفقهية،التيتعتبرمحلالاجتهادواستنباطالأحكامالشرعيةللمستجداتوالنوازل،وبالأخصقواعدوسائلالإثباتعندالمالكيةممايمثلهذاالبابالجانبالخصبللقضاةفيالفصلفيالقضاياالمطروحة؛ولهذاجاءتهذهالمذكرةلتفصلفيالقواعدالفقهيةلوسائلالإثباتالمتفقعليهاوالمختلففيهاوكيفيةالترجيحفيمابينهاعندالتعارضكالإقرارواليمينوالشهادةوالبينة،وقدخلصتالمذكرةإلىعدةنتائجوتوصياتتخدمالفقهالإسلاميفيبابالقواعدالفقهيةلوسائلالإثبات. الكلماتالمفتاحية: القواعدالفقهيةـوسائلالإثباتعندالمالكيةـالإقرارـاليمينـالشهادة. Abstract One of the most important branches of Islamic jurisprudence is the principles of jurisprudence, which are considered the basis for ijtihad (independent reasoning) and deriving legal rulings for new and unprecedented issues. Particularly, the principles of means of proof according to the Maliki school represent a fertile ground for judges in adjudicating the cases presented to them. Hence, this memorandum aims to elaborate on the jurisprudential principles of means of proof that are agreed upon and those that are disputed, and how to weigh them against each other in cases of conflict, such as confession, oath, testimony, and evidence. The memorandum concludes with several findings and recommendations that serve Islamic jurisprudence in the field of jurisprudential principles of means of proof. Keywords: jurisprudential principles, means of proof according to the Maliki school, confession, oath, testimony